2022
DOI: 10.1155/2022/4806266
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological Characterization and Estimation of Genetic Parameters of Spring Maize Hybrids in the Inner Plains of Far-West Nepal

Abstract: Heat resilient maize hybrids are an important input in maize cultivated area coupled with high temperature during the flowering period, with a specific focus on the Terai region of Nepal. The research was conducted in the Dhangadhi district from April 2020 to August 2020 in an alpha-lattice design with 26 genotypes and two replications. Analysis of variance suggests that genotypes were significantly different for all traits except plant height and plant population. The phenotypic coefficient of variation (PCV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Te distance between the cluster centroid revealed that cluster 3 and cluster 5 were farthest (highest distance) and cluster 3 and cluster 4 are closest (lowest) (Tables 7 and 8) which concludes that similarity is higher in the cluster with the lowest average distance than that of higher. A similar fnding was reported by [32].…”
Section: Correlation Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…Te distance between the cluster centroid revealed that cluster 3 and cluster 5 were farthest (highest distance) and cluster 3 and cluster 4 are closest (lowest) (Tables 7 and 8) which concludes that similarity is higher in the cluster with the lowest average distance than that of higher. A similar fnding was reported by [32].…”
Section: Correlation Analysissupporting
confidence: 88%
“…Te genotype ZH 19782 showed higher grain yield followed by multinational hybrid DKC9108, ZH19961, ZH 19940, and ZH 191965; lower grain yield was reported in genotype ZH 192252 (Table 5). Grain yield is the primary economic trait for improvement in breeding programs as they are the one dependent to yield governing traits and cause direct infuence on the productivity and proftability of farmers [32]. Several authors [16,18,24] reported that grain yield difered signifcantly in hybrid maize which provides an ample space for the selection of genotypes based on their performance.…”
Section: Reproductive Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Oyekunle et al (2015), cluster analysis is a technique that helps to identify the homogenous variables at various levels of similarity in the form of a dendrogram. In order to make selection more successful, genotypes are grouped according to how complicated they are with regard to traits (Bista et al 2022).…”
Section: Introductionmentioning
confidence: 99%